Risco ambiental e ordenamento do território em Garanhuns-PE - Melo, Felippe Pessoa de (2016)
This study aims to analyze geoenvironmental risks and their relation to spatial planning in Garanhuns - PE. The area in question has gone through intrinsic changes over the decades in its socio-spatial and environmental dynamics, emphasized by the national policy of coffee eradication in areas considered as low productivity, introduced by the then Instituto Brasileiro de Café (IBC) [Brazilian Coffee Institute] in 1965. Disruption of the field production model from agricultural to animal husbandry, immediately unleashed two phenomena on two fronts. In the field, it stimulated removal of the remaining vegetation cover to maximize pastures, therefore the implanted model was focused on animal husbandry (dairy / extensive), which also caused displacement of population groups to urban areas, since the farmer's own labor was replaced by the cowherd. In the urban area and its surroundings a sharp increase in population occurred, with emphasis on the peri-urban boundaries mostly situated on the slopes of the valleys, which have a high topographic amplitude and natural susceptibility to mass movements. The triad, spatial planning, fleeting disruption of the economical model and accelerated maximization of the urban perimeter, configured an unbalanced geoenvironmental scenario, endangering the population, especially the people who settled on the slopes and valley bottoms. To subsidize the analysis, interpretation and preparation of cartographic products relevant to the topic, this research besides conducting a survey of the state of the art of the aforementioned problems, was subsidized by geotechnologies from remote sensing and geographic information systems (GIS), using a diversified base of geospatial data. Aware that the geostatistical procedures are of paramount importance to interpolation of the information in a database (DB), kriging was chosen to be used due to its possibilistic characteristics, in other words, the maximum and minimum values added in the database are extrapolated, operationalizing the procedure of estimating possible future and past realities, and of reconstitution of current scenarios.